Tārīkh-i Āl-i Saljūq dar Ānāṭūlī - Jalalī, Nādara (Miras Maktoob, ISBN: 9789004365452., 2019)
The Saljuqs were a Turco-Muslim dynasty which ruled over Persia and parts of Central Asia and the Middle East from the 11th through the 13th century. After the death of Malikshāh I in 485/1092, the Great Saljuq empire was dissolved among his quarreling descendants, leading to the emergence of a whole series of smaller Saljuq states in Central Asia, Persia, Asia Minor, Syria, and Iraq. In Asia Minor, the Saljuqs of Rūm established themselves definitely with the coming to power of Qilič Arslan I in Konya in 485/1092. The Rūm Saljuqs continued their reign with different degrees of success, unison, and independence from other powers until the beginning of the 14th century. The present present work, a Persian history of the Saljuqs with an emphasis on the Saljuqs of Rūm, was written in Konya, around 756/1355. Rich in information, it is only second to the Mukhtaṣar of Ibn Bībī's (d. after 1285) Saljūq-nāma.